2016
DOI: 10.1007/s10067-016-3303-0
|View full text |Cite
|
Sign up to set email alerts
|

A recently developed MRI scoring system for hand osteoarthritis: its application in a clinical setting

Abstract: This study aimed to apply the recently proposed Oslo hand osteoarthritis magnetic resonance imaging (MRI) scoring system to evaluate MRI findings in a cohort of patients affected by long-standing erosive hand osteoarthritis (EHOA). Eleven female EHOA patients (median 59 [interquartile range 62-52] years, disease duration 9.5 [interquartile range 13-3.75] years) underwent MRI (1.5 T) of the dominant hand, and synovitis, bone marrow lesions (BMLs), joint space narrowing, osteophytes, cysts, malalignment, and ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
(49 reference statements)
3
20
1
Order By: Relevance
“…In case of MRI, it enables visualization of various types of damage that occur in joint, for example, cartilage lesions, cartilage thickness loss, bone marrow lesions (BMLs) and meniscal tear. According to a recent study of Ramonda et al, synovitis and BMLs detected by MRI were associated with pain, an early progression feature of erosive hand OA [9]. Even though MRI provides a diagnostic approach aiding early detection of OA, this method cannot become popular due to its high cost.…”
Section: Introductionmentioning
confidence: 99%
“…In case of MRI, it enables visualization of various types of damage that occur in joint, for example, cartilage lesions, cartilage thickness loss, bone marrow lesions (BMLs) and meniscal tear. According to a recent study of Ramonda et al, synovitis and BMLs detected by MRI were associated with pain, an early progression feature of erosive hand OA [9]. Even though MRI provides a diagnostic approach aiding early detection of OA, this method cannot become popular due to its high cost.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age for all studies was 64.4 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Most studies (n = 13) were performed on both genders, although the majority of the subjects in each study were female.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies (n = 13) were performed on both genders, although the majority of the subjects in each study were female. Only two studies [26,32] had female subjects only and one study did not report the gender of the participants [25]. Of these studies, 13 were from observational cohort studies: the Hand OSTeoarthritis in secondary care (HOSTAS) [27,[29][30][31] the Oslo hand OA cohort [18-23, 25, 32] and a clinical trial: the digital osteoarthritis in refractory hand OA (DORA) study [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…He commented on a continuum from subchondral sclerosis, osteophyte formation, to joint degradation (6). Although nowadays different methods are useful for the diagnosis of the first CMC joint, such as conventional radiology or magnetic resonance imaging (MRI), biomechanical studies on this articulation have shown that forces increase exponentially (up to 1200%) from the tip of the thumb to the CMC joint with grasp and forceful pinch with compressive forces causing pain and functional impotence in daily activities (7)(8)(9). Pain at the base of the thumb during everyday activities can cause substantial impairment in hand function.…”
mentioning
confidence: 99%